Optic nerve sheath meningocele - Juan Carlos Mesa-Gutiérrez; Silvia Muñoz Quiñones; Jorge Arruga Ginebreda (Clinical Ophthalmology, 2008)
Juan Carlos Mesa-Gutiérrez, Silvia Muñoz Quiñones, Jorge Arruga GinebredaDepartment of Ophthalmology, Hospital Universitari de Bellvitge, L’Hospitalet de Llobregat, Barcelona, SpainAbstract: A 53-year-old man presented with a 5-month history of visual loss in his left eye. Visual acuity could be corrected to 20/20 with an increased hyperopic correction. Dilated funduscopy showed faint choroidal folds and elevation of the left optic disc. The coronal view of T2-weighted magnetic resonance imaging demonstrated a fluid-filled dilated sheath surrounding normal optic nerves. General physical examination and cerebrospinal fluid analysis were normal. The subject was diagnosed as having dural ectasia of the optic nerve sheath and followed a course of acetazolamide 250 mg twice daily for three months, and displayed good anatomical and functional results during a 2-year follow-up period. Despite the fact that several authors have recommended an optic nerve decompression, most of the patients follow a benign clinical course. The role of corticosteroids is not described in the literature. Raised levels of proteins in the cerebrospinal fluid in the perioptic subarachnoidal space could be a determining factor. On the basis of an osmotic gradient between the cerebral subarachnoid space and perioptic subarachnoid space, carbonic anhydrase inhibitors could be beneficial. In contrast to other reports, we believe that surgical intervention could be reserved for patients with rapid or progressive optic nerve dysfunction.Keywords: optic nerve, perineural subaracnoid space, optic nerve meningocoele, optic nerve tumors